The Consciousness and Human Knowledge of Christ According to Lonergan and Balthasar - Pidel S.J., Aaron (Lumen et Vita, 2011)
Bernard Lonergan and Hans Urs von Balthasar both gave considerable attention to the consciousness and human knowledge of Christ. In their respective treatments of this topic, both theologians evince common tendencies. Both are at pains to develop a model of Christ’s human consciousness that 1) avoids the impression of psychological dualism, 2) acknowledges Christ to be a unique comprehensor (beholder) of the divine nature, and yet 3) shows Christ to be a true viator (wayfarer), learning and discerning in a genuinely human fashion. Lonergan does this through his model of “ineffable knowledge,” and Balthasar through “mission consciousness.” On the face of it, they seem to disagree as to whether Christ possessed the so-called visio beata (beatific vision)—with Lonergan answering affirmatively and Balthasar answering negatively. Nonetheless, because they understand the meaning of this attribution differently, it seems likely they are divided more at the level of verbal formulation than at the level of conceptual judgment. Both consciousness Christologies prove convergent and complementary.